1988
DOI: 10.1258/002367788780746575
|View full text |Cite
|
Sign up to set email alerts
|

Altered clinical and histological features of male MM mouse pyelonephritis associated with a change in its microbiology

Abstract: 35Summary Radical changes in the clinical, microbiological and histological features of spontaneous pyelonephritis in MM male mice occurred when they were transferred to a new environment after Caesarian derivation. Although the incidence of pyelonephritis remained the same, the survival age was increased. The renal histology indicated a shift to a more chronic form of pyelonephritis with renal amyloidosis as a common feature. At autopsy much more renal scarring was seen, resulting in the 'shrunken' kidney typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Possible additional genetic factors are suggested by the few MM female cases without accompanying diabetes described in this study and the higher incidence reported elsewhere (Taylor, Fraser & Bruce, 1988). The greatly diminished role of the non-swarming Proteus mirabilis in MM male UTI in EB was puzzling; it is not known how this organism displaced the swarming variety from the gut flora since the swarming type was always present in EA.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…Possible additional genetic factors are suggested by the few MM female cases without accompanying diabetes described in this study and the higher incidence reported elsewhere (Taylor, Fraser & Bruce, 1988). The greatly diminished role of the non-swarming Proteus mirabilis in MM male UTI in EB was puzzling; it is not known how this organism displaced the swarming variety from the gut flora since the swarming type was always present in EA.…”
Section: Discussionmentioning
confidence: 60%
“…Together with the faecal studies ( Table 6) this suggests that, as in humans, the bacteria found in UTI have a faecal origin. The earlier average age at death of the EA MM pyelonephritics (Tables 1 and 7) was a consequence of the acute nature of Proteus mirabilis UTI (Braude, Siemienski & Shapiro, 1960;Taylor, Fraser & Bruce, 1988). However, the average age at death of animals without renal complications is also much lower in EA.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations